Shared Care Parenting Arrangements since the 2006 Family Law Reforms - Redmond, G; Delaney, M; Rajkovic, M; Patulny, R; Katz, I; Eardley, T (My University, 2010)
The Social Policy Research Centre (SPRC) has been commissioned by the Attorney General‘s Department to undertake research on the implications of the changes to the 2006 Family Law Reforms on Shared Care Parenting, and the circumstances under which shared care arrangements work, and do not work, in the best interests of the child. This research has been undertaken in consortium with the Australian Institute of Family Studies (AIFS), and the University of Sydney Law School, and led by the SPRC.
Keywords: Government, law and policy; Government, law and policy